Recovery of Medium-Chain-Length Polyhydroxyalkanoates (PHAs) Through Enzymatic Digestion Treatments and Ultrafiltration - Yasotha, K.; Aroua, M.K.; Ramachandran, K.B.; Tan, I.K.P. (2006)
Medium-chain-length (mcl) polyhydroxyalkanoates (PHAs) are biodegradable polyesters accumulated intracellularly as energy resources by bacterial species such as Pseudomonas putida. The most popular method for PHA recovery in the downstream processing is solvent extraction using chloroform and methanol. An alternate method is bioseparation using enzymatic digestion process which eliminates the need for hazardous solvents. This research focuses on an attempt to optimize the recovery of PHAs by solubilisation of non-PHA granules through enzymatic treatments such as; Alcalase (to digest the denatured proteins), sodium dodecyl sulfate (SDS) to assist solubilisation, ethylene diamine tetra acetic acid (EDTA) to complex divalent cations and lysozyme to digest the peptidoglycan wall enveloping the cell. The experiment was designed through Taguchi's design of experiment (DOE) using Qualitek-4 software. The results show that Alcalase enzyme used had the most significant effect on the treatment process and contributed to about 71.5 in terms of process factor importance among the different factors on treatment performance for PHA recovery. It is desired to recover the PHA granules in water suspension after the enzymatic treatment by removing the solubilised non-PHA cell material through crossflow ultrafiltration system and purified through continuous diafiltration process. Final purity of PHA in water suspension obtained using GC analysis is 92.6, with a nearly 90 recovery, thus concluding that this method is indeed a suitable alternative. (c) 2006 Elsevier B.V. All rights reserved.